The Representation of Kiai Ahmad Arrifai Kalisalak in Repen Ripangi - M. Adib Misbachul Islam; Elve Oktafiyani (Insaniyat : Journal of Islam and Humanities, 2020)
This study aims to discuss the meaning of Repen Ripangi as a literary narrative manuscript of Adipati Panji Suryakusuma, Regent of Semarang which was then composed in the form of macapat song by Panji Jayasubrata. By placing it in the context of social and political history in Java in the nineteenth century, the text reveals the tension between the two social elites during the colonial period in a form of narrative poetry. This research used qualitative method with representation theory. The results show that the writing of Repen Ripangi in the form of narrative poetry was not merely an aesthetic expression of the author Javanese priayi, but also a means of representation which goal is the stigmatization of Kiai Ahmad Arrifai as a kiai who brings apprehension in society. In addition, another goal of the representation in Repen Ripangi was to strengthen of the penghulu as one of religious authorities in Java during the colonial period and the defense of priyai interests and their political patrons, namely the colonial government in Java.